OndePublicar.com: A Collaborative Web Platform about Academic Events and Journals Accepting Paper Submissions - Beckhauser, William Jones; Fileto, Renato (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2025: Anais do XL Simpósio Brasileiro de Bancos de Dados, 2025)
OndePublicar.com is a collaborative Web system that integrates dynamic information about academic events and journals, along with their Call for Papers (CFP). The system combines multiple bibliometric indicators (Qualis CAPES, SJR, SNIP), offers advanced search capabilities, and maintains a calendar of upcoming CFPs. It allows any user to suggest publication venues and CFPs, while accredited curators validate the entries. Approved entries are enriched with bibliometric data and indexed via Apache Solr, achieving a median latency of 0.47s under 10,000 concurrent queries. OndePublicar.com distinctive features include: (i) a unified repository combining a CFP calendar with national and global quality metrics of journals and events classified by field; (ii) an open, scalable architecture for venue and CFP discovery; and (iii) a collaborative curation model.